(3TQM GdegPHs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
( (3jHOC HHGH eG jhLH GdZSd(B) s
(3BNQgG (B:s
(3BNQg eHJhQ hChd GdehLhO efg ai GdMOjK Yf GdUdGI ai CQV eZUhHI bhdg (B: (3bGd GdeUfa QMeg Gdgd (B: (3hdG jLhR Cf jUdi ai CQV eZUhHI bGd GdbGVi hgPG gh GdbjGS s
(3GdfSNI HgG MhGTs
(3HChdgG Jedjc dSHW GHf MLQ SfI (B867s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs